Lymphadenectomy in elderly patients with high-intermediate-risk, high-risk or advanced endometrial cancer: Time to move from personalized cancer medicine to personalized patient medicine!. Issue 8 (August 2019) - Racin, Adélaïde; Raimond, Emilie; Bendifallah, Sofiane; Nyangoh Timoh, Krystel; Ouldamer, Lobna; Canlorbe, Geoffroy; Hudry, Nina; Coutant, Charles; Graesslin, Olivier; Touboul, Cyril; Collinet, Pierre; Bricou, Alexandre; et al.
Abstract: Background: Pelvic and paraaortic lymphadenectomy are recommended for women with high-intermediate, high-risk and advanced endometrial cancer (EC). Lymphadenectomy is less frequently performed in elderly patients than in younger patients. We examined the survival of elderly women diagnosed with high-risk EC according to whether lymphadenectomy was performed or not. Methods: We selected women over 70 years with high-intermediate risk, high-risk or advanced EC from a multicenter retrospective cohort of women diagnosed between 2001 and 2013. Multivariate logistic regression models and Cox proportional hazards survival methods for overall survival (OS), disease-free survival (DFS) and cancer-specific survival (CSS) were used for analyses. Results: 71 women had lymphadenectomy and were compared with the 213 who did not. Recurrence was similar in both groups (42% vs 33%, respectively, p = 0.17) but more deaths were reported in the group without lymphadenectomy (38% vs 23%, respectively, p < 0.001). There was no difference in adjuvant treatment in the two groups (17% vs 27%, respectively, p = 0.27). Elderly patients without lymphadenectomy had lower 3-year DFS (56% vs 71%, p = 0.076), CSS (67% vs 85%, p < 0.001) and OS (50% vs 71% p < 0.001). The Cox proportional hazard models showed independently poorer prognosis in women without lymphadenectomy (3.027, 95% CI 1.58–5.81, p < 0.001), histology type 2 (3.46, 95% CI 1.51–7.97, p = 0.003) and lymphovascular space involvement (3.47, 95% CI 1.35–8.98, p = 0.01) on 3-year CSS. Conclusion: No lymphadenectomy in elderly patients with high-risk or advanced EC is independently associated with poorer prognosis. Elderly patients with EC should benefit from lymphadenectomy when indicated.